Підвищення інноваційної сприятливості персоналу комерційної служби підприємств промислової автоматики - Дюжев, Віктор Геннадійович; Бойченко, Олег Ігорович (НТУ "ХПІ", 2017)
Стаття присвячена застосуванню інновацій в структурі управління персоналом на ринку промислової автоматики та перейняттю європейського досвіду управління. У статті розглянуті передовий світовий досвід по формуванню структури та взаємозв’язків комерційної служби на ринку компаній промислової автоматики. У статті розглянуті та проаналізовані тенденції розвитку комерційної служби, відділу навчання персоналу, основні напрямки та методі управління персоналом.

The article is sanctified to application of innovations in the structure of management a personnel at the market of industrial automation and adopting of European experience of management. In the articles considered front-rank world experience is on forming of structure and intercommunications of commercial service at the market of companies of industrial automation. In the articles considered and analysed progress of commercial department, department of studies of personnel trends, basic directions and method of management to the shots. In the real article the considered questions of transition are from regional principle of work on branch. Offer changes are in the corresponding structures of service. Set new intercommunications as into commercial service so in subdivisions that provide and serve. Drawn conclusion, that these structures it follows to perfect from position of necessities of customers in the complex systems of industrial automation.
Increase of innovative favourableness of personnel of commercial service of enterprises industrially automations
Keywords: інновації; структура управляння персоналом; навчання персоналу; personnel management; commercial service